A constitutive model for metal plastic deformation at micro/meso scale with consideration of grain orientation and its evolution. (April 2018) - Peng, Linfa; Xu, Zhutian; Gao, Zhaoyang; Fu, Ming Wang
Highlights: EBSD tests were conducted on copper sheets subjected to plastic deformation. The grain orientation effect on micro/meso scale deformation behavior was revealed. A Hall-Petch based constitutive model was proposed to include the effect. FE simulations considering polycrystal structure were performed to verify the model. Abstract: Traditional metal forming theories are not accurate in the analysis of micro/meso scale metal deformation behavior due to the so-called size effect. As the deformation process scales down to micro/meso level, the characteristics of grain orientation and its evolution play an important role in the plastic deformation which leads to the significant size effect. In this study, the tensile tests of pure copper sheet metal specimens with different grain sizes were first conducted. The flow stress is found to decrease with the increase of grain size. In addition, the specimens with coarse grain show greater scatter in flow stress and higher surface roughness due to the grain orientation effect. Furthermore, the volume fractions for three main grain orientations (<111>, <100> and <110>) were measured by electron backscatter diffraction (EBSD) both before and after the tensile tests. It is revealed that <111> is a stable orientation while the grains with the orientation of <110> tend to rotate to the orientation of <111> after deformation. Based on the experimental observations, a constitutive model with the consideration of grain orientation and its evolution was established to analyze the size effect induced. The new constitutive model was then applied in finite element (FE) simulations to characterize the influences of grain orientation and its evolution on the plastic deformation. To consider the grain heterogeneity, Voronoi tessellation was employed in the FE model establishment to simulate the polycrystalline aggregate of material. The computed results of flow stress, scatter of data and surface roughness for different grain sizes are revealed to be in accordance with the experimental results, which verify the applicability of the model established in this work. Graphical abstract: Image, graphical abstract